Regulation of Expression of the vanD Glycopeptide Resistance Gene Cluster from Enterococcus faecium BM4339 - Casadewall, Barbara (American Society for Microbiology, 2001)
A new open reading frame, encoding a putative integrase-like protein, was detected downstream from the six genes of the vanD glycopeptide resistance cluster in Enterococcus faecium BM4339 (B. Casadewall and P. Courvalin, J. Bacteriol. 181:3644–3648, 1999). In this cluster, genes coding for the VanR(D)-VanS(D) two-component regulatory system were cotranscribed from the P(R(D)) promoter, whereas transcription of the vanY(D), vanH(D), vanD, vanX(D), and intD genes was initiated from the P(Y(D)) promoter located between vanS(D) and vanY(D) (the D subscript indicates that the gene is part of the vanD operon). The VanR(D)-VanS(D) regulatory system is likely to activate transcription of the resistance genes from the promoter P(Y(D)). Glycopeptide-susceptible derivatives of BM4339 were obtained by trans complementation of the frameshift mutation in the ddl gene, restoring functional d-alanine:d-alanine ligase activity in this strain. The glycopeptide-susceptible transformant BM4409, producing only d-alanyl-d-alanine-terminating peptidoglycan precursors, did not express the resistance genes encoding the VanY(D) d,d-carboxypeptidase, the VanH(D) dehydrogenase, the VanD ligase, the VanX(D) d,d-dipeptidase, and also the IntD integrase, although the regulatory region of the vanD cluster was still transcribed. In BM4409, the absence of VanR(D)-VanS(D), apparently dependent, transcription from promoter P(Y(D)) correlated with the lack of d-alanyl-d-lactate-terminating precursors. The vanX(D) gene was transcribed in BM4339, but detectable amounts of VanX(D) d,d-dipeptidase were not synthesized. However, the gene directed synthesis of an active enzyme when cloned on a multicopy plasmid in Escherichia coli, suggesting that the enzyme was unstable in BM4339 or that it had very low activity that was detectable only under conditions of high gene dosage. This activity is not required for glycopeptide resistance in BM4339, since this strain cannot synthesize d-alanyl-d-alanine.